Myelograms - a four-year analysis in a District Hospital - Parente, Francisco; Fernandes, Aurora; Pinheiro, Beatriz; Isidoro, António (Portuguese Journal Internal Medicine, 1999)
The authors present a retrospective study of myelograms, made in patients seen in the Medicine Service of Anadia District Hospital, during a period of 4 years ljanuary 1994 to December 1997). This study involved 149 bone marrow aspirations in 133 patients. The authors study the morbility of the exam, indications for myelogram, haematologic peripheral counts, quality and results of the marrow smear, haematologic and non-haematological diagnoses, myelogram contribuition to the patient diagnosis and therapy. ln conclusion, they outline the advantages of this examination to an Internal Medicine Department, contributing to the detection of haematologic diseases and resulting in early therapeutic orientation.